EL "CERCANO OESTE" DE LOS ESTADOS UNIDOS: Las Economías Dinámicas de Asia del Este - Drobnick, Richard (1997)
It examines the process of opening up Asian markets to US participation, which occurred as a result of technological, ideological and individual changes. These changes contribute to regional economic integration, reason for which US companies doing business in Asia should develop regional strategies and not view Asian countries as completely separate markets. Five factors are pointed out that explain the growth of exports of US companies to East Asia: increasing competitiveness in prices, increasing competitiveness in the quality of goodness, increasing openness of Asian markets, corporate commitments to international business opportunities, and continued high economic growth in Asian markets. It is concluded that US organizations should learn about the cultural and institutional characteristics of Asian markets in order to be able to interact more effectively with Asian partners and competitors.